Crystallinity Preservation and Ion Migration Suppression through Dual Ion Exchange Strategy for Stable Mixed Perovskite Solar Cells. Issue 15 (3rd May 2017) - Zhang, Tiankai; Long, Mingzhu; Yan, Keyou; Qin, Minchao; Lu, Xinhui; Zeng, Xiaoliang; Cheng, Chi Man; Wong, Kam Sing; Liu, Pengyi; Xie, Weiguang; Xu, Jianbin
Abstract : The mixed perovskite (FAPbI3 )1− x (MAPbBr3 ) x, prepared by directly mixing different perovskite components, suffers from phase competition and a low‐crystallinity character, resulting in instability, despite the high efficiency. In this study, a dual ion exchange (DIE) method is developed by treating as‐prepared FAPbI3 with methylammonium brodide (MABr)/tert‐butanol solution. The converted perovskite thin film shows an optimized absorption edge at 800 nm after reaction time control, and the high crystallinity can be preserved after MABr incorporation. More importantly, it is found that the threshold electrical field to initiate ion migration is greatly increased in DIE perovskite thin film because excess MABr on the surface can effectively heal structural defects located on grain boundaries during the ion exchange process. It contributes to the over‐one‐month moisture stability under ≈65% room humidity (RH) and greatly enhanced light stability for the bare perovskite film. As a result of preserved high crystallinity and simultaneous grain boundary passivation, the perovskite solar cells fabricated by the DIE method demonstrate reliable reproducibility with an average power conversion efficiency (PCE) of 17% and a maximum PCE of 18.1%, with negligible hysteresis. Abstract : A dual ion exchange (DIE) method is developed for mixed perovskite thin films by treating trigonal FAPbI3 with MABr in tert‐butanol. This DIE method can preserve the initial high crystallinity and passivate vacancies/defects at grain boundaries, leading to enhanced moisture and illumination stability and reduced ion migration. The solar cell device using the DIE method achieves the highest power conversion efficiency of 18.1%, with negligible hysteresis.